(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores modern approaches to learning English that enable learners to achieve a high level of language proficiency in the shortest possible time. Special attention is paid to the use of technology, communicative methods, and self-directed learning. The results of a study conducted among students learning English are presented, along with recommendations for optimizing the learning process. The article will be useful for both teachers and students looking to improve their language skills.